Stimuli involved in dental anxiety: What are patients afraid of?: A descriptive study. Issue 3 (29th November 2019) - Vanhee, Tania; Mourali, Sandrine; Bottenberg, Peter; Jacquet, Wolfgang; Vanden Abbeele, Astrid
Abstract: Background: Dental anxiety is a psychological response inducing aversion following a dental ill‐defined stimulus, non‐imminent and perceived as potentially dangerous. It is better to intervene during childhood than to resolve in adulthood when dental anxiety is more settled. Aim: The purpose of this study is to determine the nature of dental anxiety‐provoking stimuli in young patients. Design: A questionnaire was submitted to 566 children between 3 to 18 years in health institutions and schools in Brussels, Belgium. The items were divided into 3 groups: environment (ENV), local anaesthesia (LA), and intervention (INT) and summarized through averaging per group. Descriptive analysis and non‐parametric testing were combined with logistic regression after discretization, above mild, for the group averages. Results: About 7.2% of the respondents expressed high to severe dental anxiety. Several items presented a clear bimodal distribution dividing the population in fearless and fearing patients, for example, sight and feel of the syringe, sight and taste of blood and extraction. Others presented with a gradually lower incidence with increasing fear level. Fear for the environment was generally low. Gender and ethnic origin contribute significantly to the prediction of fear caused by LA. For fear caused by INT, first the place of questioning enters the models, thereafter follow: negative experience, frequency of dental visit, and gender ( P  < .05). Conclusions: While the dental environment is in general not causing fear, the invasive part of the anaesthesia and the invasive dental procedures are involved. Fear seems to be related to culture, previous experience, and gender.